Likelihood analysis of the CfA2+SSRS2 and of the Las Campanas redshift surveys - Palladino, Emilia; Amendola, Luca (Arxiv, 2001)
We present the results from the correlation analysis of two galactic redshift surveys, the extended CfA2+SSRS2 and the slice centered on $δ=-12^{°}$ of Las Campanas. Furthermore, we evaluate the likelihood confidence regions for the CDM model and for the fractal model parameters. Our results indicate that, although the CDM model is in good agreement with the data, the fractal description cannot be ruled out, because of its intrinsic high variance.